As diferenças entre as legislações municipais referentes a pólos geradores de viagens e sua contribuição para a legislação de Fortaleza - Gifoni, Emiliana Araújo (2006)
The implementation of Traffic Generation Centers (TGC’s), normally comes occurred of impacts in diverse scopes around the enterprise, as congestions, overall increase of the time of displacement of the people, deterioration of the environment and the constructions, for the increase of pollutions, both noise and air; still compromises the security of the vehicles, bike riders and pedestrians, with the ever-increasing number of traffic accidents. In order to prevent these consequences to the urban setting, in the last years has been used, beyond the norms of legislation for TGC's, models of impact study on transportation systems, aiming to determine the impacts on the resultant traffic and circulation of this implementation of the enterprise, allowing the identification of the intervention necessities, besides providing the access and reducing the impacts associates to the enterprise. In Brazil, due to lack of standardization and the inexistence of the legislation for TGC's in some states and cities, diverse models of reports, all based on the parameters of the respective effective legislations of zoning and land use. The inexistence of legislation and the variety of impact model reports makes the analysis process difficult and control of TGC's in the urban setting, generating the set free implementation of these TGC's. This work analyzes the existing aspects in some cities and absentees in others, and forms to contribute a methodology of impact evaluations for TGC's, in its legal scope, better adjusted to the reality of Fortaleza, but also can contribute to the perfection of existing methodologies in other cities.